Vaccination as a strategy for Chlamydia trachomatis control: a global mathematical modeling analysis - Monia Makhoul; Laith J. Abu-Raddad (BMC Global and Public Health)
Abstract Background Chlamydia trachomatis (CT) is among the most common sexually transmitted infections and is associated with substantial health and economic burdens. Vaccination may offer a promising strategy for its global control. Methods A deterministic, age-structured mathematical model was applied to assess the global impact of a hypothetical CT vaccine. The analysis explored a range of assumptions for vaccine efficacy against infection acquisition ( $${VE}_{S}$$ VE S ), duration of protection, and coverage, across both adult catch-up and adolescent-targeted vaccination strategies. Results Vaccinating individuals aged 15–49 years beginning in 2030 with a vaccine of $${VE}_{S}=50%$$ VE S = 50 % and 20-year protection, scaled to 80% coverage by 2040, reduced global CT prevalence, incidence rate, and annual new infections in 2050 by 26.2%, 32.3%, and 26.5%, respectively. Cumulatively, 717 million infections were averted by 2050. The number needed to vaccinate (NNV) to prevent one infection declined from 23.3 in 2035 to 10.6 in 2050, with variation across population groups: 5.9 for those aged 15–19 years, 7.5 for those aged 10–14 years, and 3.0 for high-risk groups. Vaccine impact increased with higher $${VE}_{S}$$ VE S , longer protection duration, and inclusion of breakthrough effects on infectiousness and infection duration. While adolescent vaccination achieved substantial impact, its benefits accrued more slowly than those of adult-targeted strategies. Conclusions Vaccination against CT can substantially reduce global infection burden, even with moderate efficacy. Impact is enhanced by targeted strategies, with adolescent vaccination aiding long-term control and catch-up programs ensuring immediate benefit. These findings highlight the urgency of vaccine development and integration into public health efforts.